THE EFFECT OF USING A DIGITAL-BASED COMMUNICATION LEARNING GUIDE FOR AUTISM CHILDREN ON PARENTS UNDERSTANDING WHEN TRAINING COMMUNICATION IN AUTISM CHILDREN - Wulan Utami; Agus Kristiyanto; Joko Yuwono (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2024)
The background to this research is the lack of understanding of parents in assisting children with autism in learning to communicate at home. This is due to the lack of references and inappropriate learning assistance methods. Parents need proper guidance to assist children with autism in learning to communicate at home. This research aims to determine the effect of using a digital-based communication learning guide for autistic children on parents' understanding when training communication for autistic children. This research uses a Research and Development (R&D) approach with the ADDIE development model. The subjects in this study were 24 parents of autistic children. The data collection technique uses a multiple-choice objective test with a total of 15 questions. The data analysis technique uses non-parametric statistics with the Wilcoxon Sign Rank Test with the help of SPSS 29. The results of data analysis obtained a scale value of ?ℎ????? = -4,299 with Asymp. Sig. (2-tailed) <.001. The probability value in Zcount is then compared with the significance level α = 0.05. There is a significant difference between the pretest and posttest results with P 0.01, which is smaller than the significance level of 0.05 or 5%. Thus Ho is rejected and Ha is accepted. Based on the results of the research analysis, it was concluded that there was a significant influence on the use of digital-based communication learning assistance guides for autistic children for parents in increasing parents' understanding when training communication for autistic children.